Developing strategies for stabilizing the livelihood of smallholder farmers through non-farm activities: the application of the SWOT-AHP-TOWS analysis - Baghernejad, Jafar; Sabouri, Mohammad Sadegh; Shokati Amghani, Mohammad; Norozi, Abbas (Frontiers in Sustainable Food Systems, 2023)
Non-farm activities are a means of livelihood stabilization and are regarded as a sustainable approach to bringing balance to the economic, social, cultural, and environmental aspects of sustainable livelihood. This research aims to develop strategies for stabilizing the livelihood of smallholders through non-farm activities using a combined SWOT-AHP-TOWS model. The results of analyzing the strategic space for developing strategies for stabilizing the livelihood of smallholders through non-farm activities revealed that the strengths (0.391) were more than the weaknesses (0.276) in the internal space and that the opportunities (0.195) were more than the threats (0.138) in the external space. Also, it was found that the internal challenges (S + W = 0.667) were more important than the external challenges (O + T = 0.33) in developing livelihood stabilization strategies. Further, the results showed that the beneficial space (O + S = 0.586) dominated the risky space (T + W = 0.414). Eventually, 20 strategies were developed among which the most important ones were "establishing and developing greenhouse cultivation based on the crop patterns considering the relative advantages of the villages" and "establishing microcredit foundations and funds to support the youth in getting involved in rural non-farm businesses." In general, the results can provide new insights into the stabilization of the livelihood of smallholders through non-farm activities.